Impact of KRAS status on tumor response and survival after neoadjuvant treatment of locally advanced rectal cancer. Issue 1 (6th October 2020) - Zhou, Peige; Goffredo, Paolo; Ginader, Timothy; Thompson, Dakota; Hrabe, Jennifer; Gribovskaja‐Rupp, Irena; Kapadia, Muneera; Hassan, Imran
Abstract: Background: Mutation of the KRAS oncogene (m KRAS ) in colorectal cancer has been associated with aggressive tumor biology, resistance to epidermal growth factor inhibitors, and decreased overall survival (OS). The aim of the current study was to analyze the association of m KRAS with pathologic complete response (pCR) and neoadjuvant rectal (NAR) score, and its impact on the survival of patients with locally advanced rectal cancer who were managed with multimodality therapy. Methods: The National Cancer Database was queried for stage II–III rectal cancer patients with a known KRAS status who underwent neoadjuvant chemoradiation therapy (nCRT) and proctectomy between 2004 and 2015. Results: In total, 1886 patients were identified; 12% had pCR and 36% had m KRAS . Patients with m KRAS were more likely to have advanced pathologic T stage, tumor deposits, perineural invasion, and elevated carcinoembryonic antigen levels (all p  ≤ .05). After adjustment for available confounders, m KRAS status was not associated with pCR or NAR score. In multivariable analysis, patients with pCR and lower NAR score had better OS, whereas m KRAS was independently associated with a worse prognosis. Conclusion: In this cohort of locally advanced rectal cancer patients who underwent proctectomy after nCRT, m KRAS was not associated with lower pCR rates or NAR scores; however,  these patients experienced worse survival.